P07.17 Changes of biomarkers in a msm hiv infection indicate the requirements of both antigen and antibody tests for early diagnosis. (13th September 2015) - Gu, W; Hu, Y; Hu, W; Xu, B
Abstract : Background: Early diagnosis of human immunodeficiency virus (HIV) infections has significant impact in HIV controls. This case report aimed to examine changes of biomarkers in an acute HIV infection in a man who had sex with men (MSM), and to suggest laboratory tests for early detection of HIV infections. Methods: The patient presented himself to a specialised hospital. Information on sexual activities, symptoms and signs were collected during the consultation. Repeated measurements of HIV viral-load, p24 antigen-antibody complex, and lymphocyte subsets were undertaken. Tests for HIV genotypes and drug resistance were also conducted. Results: The patient, a MSM, sought medical care 8 days after the onset of low fever and sore throat. The last unprotected MSM sex activity occurred 20 days prior to the onset of the symptoms. Physical examination revealed periodontitis and torso rash. The p24 antigen was positive on the 1 st visit and titers declined to undetectable 10 days after the 1 st visit. HIV antibody was absent until 10 days after the 1 st visit, and confirmatory test (Western Blot) was negative until 20 days after the 1st visit. CD4/CD8 ratios decreased over the course of clinical observation. HIV viral load was at the highest on the 1 st visit and declined afterwards. The HIV virus had a genotype of CRF 01_AE. Conclusion: In clinical practice, a combination of HIV antigen-antibody tests is required for early detection of HIV infections. Disclosure of interest statement: This work was supported by the Shanghai Nature Science foundation (#09DZ1907104) and a Distinguished Professorship Award to the corresponding author granted by the China Medical Board (No. G16916403). The funding agencies had no role in the design or execution of the study, nor in the interpretation or publication of its results.